2007
DOI: 10.1111/j.1365-294x.2007.03396.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean populations of the lesser white‐toothed shrew (Crocidura suaveolens group): an unexpected puzzle of Pleistocene survivors and prehistoric introductions

Abstract: An earlier study revealed the strong phylogeographical structure of the lesser white-toothed shrew (Crocidura suaveolens group) within the northern Palaearctic. Here, we aim to reconstruct the colonization history of Mediterranean islands and to clarify the biogeography and phylogeographical relationships of the poorly documented Middle East region with the northern Palaearctic. We performed analyses on 998-bp-long haplotypes of the mitochondrial cytochrome b gene of 143 samples collected around the Mediterran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 54 publications
2
50
1
Order By: Relevance
“…Several mammalian species have been studied to identify the genetic link between insular and mainland populations (Santucci et al, 1998;Pierpaoli et al, 1999;Cosson et al, 2005;Dubey et al, 2007aDubey et al, , 2008. From these and other studies, it can be concluded that modalities of island colonization are very diverse according to the island and/or species under study, leading to a complex pattern of mammalian composition representing endemic, native or introduced species (Masseti, 1998;Sarà, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several mammalian species have been studied to identify the genetic link between insular and mainland populations (Santucci et al, 1998;Pierpaoli et al, 1999;Cosson et al, 2005;Dubey et al, 2007aDubey et al, , 2008. From these and other studies, it can be concluded that modalities of island colonization are very diverse according to the island and/or species under study, leading to a complex pattern of mammalian composition representing endemic, native or introduced species (Masseti, 1998;Sarà, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Amplification conditions consisted of 35 thermal cycles of 30 s denaturation (60 s for the set L14841/H15915) at 94°C, 45 s annealing (60 s, L14841/H15915) at 50°C, and 60 s (120 s, L14841/ H15915) extension at 72°C. For details on DNA purification and cycle sequencing see Dubey et al (2007a).…”
Section: Sampling Extraction and Dna Amplificationmentioning
confidence: 99%
“…Estimation of the divergence time from the molecular data was performed according to a calibration developed previously for the Soricidae by Fumagalli et al (1999), and that allowed fully coherent results in a biogeographic point of view (see, e.g., Vogel et al, 2003;Brändli et al, 2006;Cosson et al, 2005;Dubey et al, 2006Dubey et al, , 2007a. This calibration is based on an estimate of 20 million years for the split between Crocidurinae and Soricinae shrews, and it was developed considering the cytochrome b sequence divergences based on third position transversions, with a rate of 1.36%/Myr (95% confidence interval: 1.08-1.64%/ Myr).…”
Section: Molecular Clock Analysesmentioning
confidence: 99%
See 2 more Smart Citations